Optimasi Metode Travelling Salesman Problem (TSP) Dalam Menyelesaikan Kasus Rute Terpendek Pengiriman Barang - M, Padma Mike Putri (LPPM UNIKA Santo Thomas Medan, 2023)
The process of searching and tracking is very important in determining the success of the basic concepts of artificial intelligence. One science that is able to solve the shortest route concept is the Traveling Salesman Problem (TSP) Algorithm. The work form of this algorithm is in the form of determining the shortest route with the work process calculating all paths passed using predetermined concepts and rules. The form of the Traveling Salesman Problem (TSP) is in the form of a minimum weight on a connected graph, with the basic concept of visiting several cities and returning to the original city so that each city is visited exactly once with the shortest possible total distance traveled. The problem of this research is the lack of understanding Salesman in understanding algorithms that are able to provide instructions for the shortest path so that it is easy to find solutions in the form of information that can be used as a reference in saving time and costs on the way. The main objectives of this research are (1) to determine the route of delivery of goods, (2) to solve the Traveling Salesman Problem (TSP) algorithm, (3) to save time and money while traveling. The final results of this study found 24 paths that could be passed by salesmen. Each route has a different value. The value of the shortest route that can be used as a reference is the JLMK/KMLJ line. JLMK route value = 60 +40+40=160 and KMLJ route = =40 +40+60=140. The value of the shortest route found is a route point of 140.